The Prediction Ability of Emotional Regulation in Self-Compassion and Self-Esteem among Jordanian Substance Abusers - Al-Ziadat, Mariam (Dirasat: Educational Sciences, 2021)
This study aims to reveal the level of emotional regulation, self-compassion, and self-esteem among substance abusers in Jordan, and to examine the predictive ability of emotional regulation in both self-compassion and self-esteem among them. The study followed the correlational descriptive approach, the sample consisted of 120 substance abusers in Jordan, all of them males. They were randomly selected from addiction treatment centers in Jordan. Three instruments were used: the difficulties in emotion regulation scale, self-compassion scale, and self-esteem scale which were modified to the Jordanian Environment. The reliability and validity of these scales were suitable. To answer the questions of the study Means, Deviation Standards, and linear Regression were used. The results of the study indicated that there was a statistically significant negative relationship at the significance level (0.05) between the difficulties with emotional regulation and both self-compassion and self-esteem, and also indicated that the difficulty with emotional regulation explains 28% of self-compassion and explains 15% of self-esteem. The results of the study also indicated the average level of difficulties with emotional regulation and self-compassion, as well as the self-esteem of substance abusers in Jordan. The study concludes that attention should be paid to preparing preventive and curative programs for substance abusers that develop emotional regulation processes for them.